2010
DOI: 10.1016/j.bmc.2010.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of goniothalamin on the development of Ehrlich solid tumor in mice

Abstract: In this work the antiproliferative activity of goniothalamin (1), both in racemic and in its enantiomeric pure forms, in a solid tumor experimental model using laboratory animals is described. The antiedematogenic activity displayed by racemic 1 in the carrageenan edema model in mice together with the reduction of Ehrlich solid tumor model suggest a relationship between anticancer and antiinflammatory activities with the antiinflammatory activity favoring the antiproliferative activity itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 28 publications
4
59
0
5
Order By: Relevance
“…Also, other studies demonstrated pro-apoptotic activity of the R-GTN by means of caspases pathway; increase of BAX pro-apoptotic protein expression; and inhibition of nitric oxide synthase (NOS) (Inayat-Hussain et al 2003, de Fatima et al 2005. Vendramini-Costa et al (2010) verified that racGTN, the same used in the study herein, showed antiedematogenic activity with simultaneous tumoral development inhibition in the solid tumor of Ehrlich. The same authors observed similar action between racGTN and the Piroxicam, nonsteroidal and anti-inflammatory, by means of significant inhibition of the inflammatory edema in an Ehrlich tumor.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Also, other studies demonstrated pro-apoptotic activity of the R-GTN by means of caspases pathway; increase of BAX pro-apoptotic protein expression; and inhibition of nitric oxide synthase (NOS) (Inayat-Hussain et al 2003, de Fatima et al 2005. Vendramini-Costa et al (2010) verified that racGTN, the same used in the study herein, showed antiedematogenic activity with simultaneous tumoral development inhibition in the solid tumor of Ehrlich. The same authors observed similar action between racGTN and the Piroxicam, nonsteroidal and anti-inflammatory, by means of significant inhibition of the inflammatory edema in an Ehrlich tumor.…”
Section: Discussionsupporting
confidence: 74%
“…Celecoxib was obtained from CELEBRA (Pfizer Pharmaceuticals LLC, Caguas, Puerto Rico), and diluted in CMC 0.05% (Sozer et al 2011). The acute toxicity of GTN has been evaluated in a previous study (Vendramini-Costa et al 2010).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goniothalamin is a promising antitumor agent against cancerous cell lines (Wattanapiromsakul et al, 2005). On the other hand a study by Vendramini-Costa et al , 2010 demonstrated that the antiproliferative activity of goniothalamin in some solid tumor experimental model with no evidence of toxic effects in the animals after single and repeated doses.…”
Section: Introductionmentioning
confidence: 99%
“…e dose used to test the antitumor activity of the extracts was 10% of the LD 50 ; at these doses, no histological changes were observed in mice treated for seven days. So, these doses were considered safe for use in the following in vivo experiments [18].…”
Section: Column 3: Hexanic Extractsmentioning
confidence: 99%